The Fall of Muammar Gaddafi and the Contemporary Security Debacle in West Africa: An Examination of Interconnectedness - Oladimeji, Talibu (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022DO - 10.58709/niujss.v8i1.1414, 2022)
West Africa is a home of seventeen countries which are divided by colonial alienation. The region has three principal divisions i.e. Luzophone, Francophone and Anglophone and this imperial division dictates the direction of social and political events in the region. In terms of security architecture, the region is one of the most volatile areas of the international security concerns; and such security is dictated by exogenous issues. One of these exogenous issues is the fall of Gaddafi's Libya in 2011 and the attendant itinerant soldiers in the Sahel region of West Africa. Thus, this research examines the connection between the fall of Libya and the contemporary security challenges in the West Africa sub region. It seeks to discuss the role of Sahel region's seeming anarchical situation with the current security complications in West Africa sub region. In conducting this research, the theoretical precept of Regional Security Complex (RSCT) is employed to unravel the interconnectedness of the insecurity wave in the region. In addition, the research employed the use of latent content analysis to mine data from relevant sources. Keywords: Security, Sahel, Libya, West Africa, Muammar Gaddafi